Matching Mirage Beneficiaries "Their Personal, Social and Economic Characteristics and Ways to implementing them in Light of General Practice in Social Work" - Al Hammadi, Hammad Ali Saleh (Journal of Humanities & Social Sciences, 2021)
The study aimed to identify the personal, social and economic characteristics of those registered in the Mirage matching unit, as well as trying to reach suggested recommendations in light of the general practice of developing the mechanisms of the matching services in family development associations. The researcher relied in this study on the descriptive approach analyzes secondary data through a comprehensive enumeration of those wishing to marry at the Ibn Baz Association for Family Development. The study found that the vast majority of applicants for matching services are Saudi men, as well as for women. The study also found that more than half of the sample are males from the central region, and thier ages range from 31 to less than 35 years. It was found that more than a third of the sample are holders of a bachelor’s degree, and nearly a quarter of the sample are of high school holders. The majority of the respondents are governments employees, and it was found that nearly a quarter of the sample are employees in the private sector. The nature of the work of female applicants mostly were students. The study also found that most of the respondents have an income between 7001 to 15,000 thousand riyals, and nearly half are married males. As for female applicants, it was found that the vast majority had never been married. Formulate professional processes for general practice with individuals, families, groups, institutions, and societies accordingly.
Keywords: conciliation; those who want to marry; characteristics; general practice